2020
DOI: 10.1016/j.vas.2020.100096
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary Marula nut meal on the physical properties, proximate and fatty acid content of Japanese quail meat

Abstract: Soyabean meal (SBM) is the major dietary protein source for the poultry industry in sub-Saharan Africa. Due to inadequate local soyabean production, alternative protein sources are required. Two hundred 9-day old Japanese quail chicks were randomly allocated to grower diets wherein Marula nut meal (MNM) substituted SBM on a crude protein (CP) basis at 0%, 25%, 50%, 75% and 100% and fed for 4 weeks, followed by being fed on similarly formulated finisher diets for 2 weeks, and thereafter they were humanely slaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
1
3
1
1
Order By: Relevance
“…In terms of meat quality, the increased redness in contrast to decreased hue angle of broiler meat at 45 min post-slaughter may be a response to dietary MSC. Corroborating our results, Mazizi et al ( 2020 ) also observed increased breast meat redness in Japanese quails fed incremental dietary levels of MSC at 24 h post-slaughter whilst Mthana et al ( 2022 ) observed no colour changes in meat from broiler chickens fed MSM-supplemented diets. The increased redness may have been induced by the high iron and protein contents of MSC (Malebana et al 2018 ) that would have enhanced the meat myoglobin content.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of meat quality, the increased redness in contrast to decreased hue angle of broiler meat at 45 min post-slaughter may be a response to dietary MSC. Corroborating our results, Mazizi et al ( 2020 ) also observed increased breast meat redness in Japanese quails fed incremental dietary levels of MSC at 24 h post-slaughter whilst Mthana et al ( 2022 ) observed no colour changes in meat from broiler chickens fed MSM-supplemented diets. The increased redness may have been induced by the high iron and protein contents of MSC (Malebana et al 2018 ) that would have enhanced the meat myoglobin content.…”
Section: Discussionsupporting
confidence: 89%
“…caffra ) seed kernels, MSC, is similar to SBM in its CP content (470 g/kg DM) (Mlambo et al 2011 ; Mdziniso et al 2016 ) and profile of essential and non-essential amino acids with substantial residual oil that is rich in n -9 monounsaturated fatty acid (MUFA) oleic acid (72% to 85%) (Mthiyane and Mhlanga 2017 ). Among non-ruminant animals, it has been investigated as an alternative to SBM in the diets of Japanese quails (Mazizi et al 2020 ), pigs (Malebana et al 2018 ; Thabethe et al 2022 ), and broiler chickens (Manyeula et al 2022 ; Mthana et al 2023 ). Nutritionally, the major limitation of MSC is its deficiency of the essential amino acid lysine (Mthiyane and Mhlanga 2017 ; Malebana et al 2018 ), the second most limiting amino acid in maize-SBM-based diets after the sulphur amino acid methionine (Dozier et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low density lipoproteins are linked to cardiovascular risk in humans. Oleic acid is known for reducing the risk of cholesterol accumulation [ 50 ] in humans by increasing HDL-cholesterol in blood. The high oleic acid content in the Longissimus dorsi muscle of lambs fed MKCD is attributed to some oleic acid from the diet escaping rumen biohydrogenation and being absorbed in the small intestine for tissue assimilation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perbedaan fase pertumbuhan pada puyuh menyebabkan adanya perbedaan kebutuhan zat pakan (Radhitya, 2015). Komposisi bahan pakan yang dikonsumsi oleh puyuh jepang pada masa pertumbuhan akan mempengaruhi pembentukan otot (Mazizi et al, 2020). Penelitian Widodo dkk., (2013)…”
Section: Pendahuluanunclassified